2004
DOI: 10.1021/ic0494051
|View full text |Cite
|
Sign up to set email alerts
|

Clioquinol, a Drug for Alzheimer's Disease Specifically Interfering with Brain Metal Metabolism:  Structural Characterization of Its Zinc(II) and Copper(II) Complexes

Abstract: Clioquinol, a 8-hydroxyquinoline derivative, is producing very encouraging results in the treatment of Alzheimer's disease (AD). Its biological effects are most likely ascribed to complexation of specific metal ions, such as copper(II) and zinc(II), critically associated with protein aggregation and degeneration processes in the brain. We report here, for the first time, a structural characterization of the zinc(II) and copper(II) complexes of clioquinol. A ligand to metal stoichiometry of 2:1 is found in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
168
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(180 citation statements)
references
References 22 publications
11
168
0
1
Order By: Relevance
“…Indeed, no subsequent clinical trials have observed SMON in participants treated with clioquinol. Clioquinol has a moderate affinity for iron, copper, and zinc (Kd Cu is 1.2×10 -10 M, Kd Zn is 7×10 -8 M) [197], and for this reason it was explored as a drug for AD. Although it was initially considered a chelator [198][199][200][201], it has more recently been characterized as a copper/zinc ionophore, which functions to redistribute these metals into cells [196,[202][203][204][205][206].…”
Section: Clioquinol and Pbt2mentioning
confidence: 99%
“…Indeed, no subsequent clinical trials have observed SMON in participants treated with clioquinol. Clioquinol has a moderate affinity for iron, copper, and zinc (Kd Cu is 1.2×10 -10 M, Kd Zn is 7×10 -8 M) [197], and for this reason it was explored as a drug for AD. Although it was initially considered a chelator [198][199][200][201], it has more recently been characterized as a copper/zinc ionophore, which functions to redistribute these metals into cells [196,[202][203][204][205][206].…”
Section: Clioquinol and Pbt2mentioning
confidence: 99%
“…Based on these results we employed the same functional and 378 basis set to investigate the structures of Cu(8-HQH) 2 and Cu(8-HQS) 2 , and compared 379 the results to the reported 1:2 metal:ligand structure for Cu(CQ) 2 . 87 The X-ray metricals 380 for Cu(CQ) 2 and the computed values are shown in Table 4. The predicted coordination 381 0.06 Å of the reported data for Cu(CQ) 2 .…”
Section: Theoretical Calculations Of the Cu II Complexes 372mentioning
confidence: 99%
“…Clioquinol is a lipohilic compound that is able to form stable complexes with copper (II) ions (135). To test this, we mixed CQ and CuCl 2 in a 1:1 molar ratio and an observable color change occurred, indicating that a chemical reaction had taken place (136).…”
Section: Clioquinolmentioning
confidence: 99%